Love to hate you : a novel - Adair, Marina (8th Note Press, 2025)
A modern twist on You've Got Mail starring an indie bookstore owner looking for true love and a cynical CEO who may ruin everything, from New York Times bestselling author Marina Adair. Summer Russo believes in the power of destiny and true love . . . which might be why she sank her entire life savings into reviving a nearly-bankrupt independent bookstore that specializes in romance novels and beach reads. But just as she starts to get the hang of the new business, a big-box bookstore moves in next door, run by the grumpy and arrogant Kingston, who seems determined to ruin her day (and her livelihood). Wes Kingston is a cut-throat CEO who doesn't believe in love - or failure. He runs his business the way he runs his life: alone. And he isn't going to let a fiery femme fatale take him down. Especially when she is dead set on stopping the opening of his new bookstore. At least Summer has her family's annual vacation in Mystic, CT to look forward to as a break from the standoff. But when she arrives at the beachside cabin, she realizes that her usual summer respite may not be so carefree after all. Her sister has brought along not only her boyfriend but his brother, who just happens to be the very same surly-but-infuriatingly-sexy bookstore mogul Summer thought she was getting away from. The bookstore war is still on, and neither Summer nor Kingston will go down without a fight. But when one thing leads to another and fighting turns to foreplay, both find themselves stuck in a battle for the bookstore - and for their hearts.